Ethyl 8-amino-6-bromoimidazo[1,2-a]pyridine-2-carboxylate - Siham Dahmani; Youssef Kandri Rodi; Santiago V. Luis; El Mokhtar Essassi; Lahcen El Ammari (Acta Crystallographica Section E, 2011)
There are two independent molecules in the asymmetric unit of the title compound, C10H10BrN3O2, which are linked by N—H...O and C—H...O hydrogen bonds. The fused ring systems in both molecules are nearly planar with maximum deviations of 0.001 (3) and 0.029 (3) Å. All non-H atoms of the first molecule are approximately co-planar whereas in the second molecule, the ethyl group is almost perpendicular to the imidazo[1,2-a]pyridine system, the C—O—C—C torsion angles in the carboxylic acid ethyl group being −179.8 (4) and 112.1 (5)°, respectively.